2001
DOI: 10.1128/jvi.75.19.9018-9028.2001
|View full text |Cite
|
Sign up to set email alerts
|

Three Herpes Simplex Virus Type 1 Latency-Associated Transcript Mutants with Distinct and Asymmetric Effects on Virulence in Mice Compared with Rabbits

Abstract: Herpes simplex virus type 1 latency-associated transcript (LAT)-null mutants have decreased reactivation but normal virulence in rabbits and mice. We report here on dLAT1.5, a mutant with LAT nucleotides 76 to 1667 deleted. Following ocular infection of rabbits, dLAT1.5 reactivated at a lower rate than its wild-type parent McKrae (6.1 versus 11.8%; P ‫؍‬ 0.0025 [chi-square test]). Reactivation was restored in the marker-rescued virus dLAT1.5R (12.6%; P ‫؍‬ 0.53 versus wild type), confirming the importance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…If Egr-1 increases HSV-1 replication in cells through repressing LAT, the replication of LAT deletion mutants in cells should be increased compared with that of wild-type viruses. However, our results found that the replication of 2 LAT deletion mutants, dLAT2903 (22) and dlLAT1.8 (23), and their wild-type viruses, McKrae and KOS, was comparable in SK-N-SH cells (data not shown), which is consistent with previous studies using other cell lines (22,23). These results indicate that Egr-1 functions to increase HSV-1 replication in cells in a LAT-independent manner.…”
Section: Egr-1 Activates the Productive Cycle Gene Promoters Of Hsv-1supporting
confidence: 83%
“…If Egr-1 increases HSV-1 replication in cells through repressing LAT, the replication of LAT deletion mutants in cells should be increased compared with that of wild-type viruses. However, our results found that the replication of 2 LAT deletion mutants, dLAT2903 (22) and dlLAT1.8 (23), and their wild-type viruses, McKrae and KOS, was comparable in SK-N-SH cells (data not shown), which is consistent with previous studies using other cell lines (22,23). These results indicate that Egr-1 functions to increase HSV-1 replication in cells in a LAT-independent manner.…”
Section: Egr-1 Activates the Productive Cycle Gene Promoters Of Hsv-1supporting
confidence: 83%
“…The HSV-1 LAT locus includes several microRNAs, at least two of which affect expression of a viral protein (54). However, these microRNAs all map outside the first 1.5 kb of the primary 8.3-kb LAT transcript, which is the region of LAT that we previously demonstrated was both sufficient and required for LAT's ability to enhance the reactivation phenotype in mouse or rabbit models of infection (9,55,56). Thus, these microRNAs are unlikely to be involved in enhancing latency/reactivation in these animal models.…”
Section: Discussionmentioning
confidence: 99%
“…dLAT2903 contains a deletion from Ϫ161 to ϩ1667 relative to the start of the primary 8.3-kb LAT and thus does not express detectable levels of LAT (48,49). Unlike the wild-type (wt) strain of McKrae, dLAT2903 does not induce high levels of spontaneous reactivation in rabbits (48,49) or high levels of induced reactivation in mice (46). The spontaneous reactivation phenotype of dLAT2903 in rabbits and the explant-induced reactivation phenotype of dLAT2903 in mice are restored to wildtype levels when the first 1.5 kb of LAT (LAT nucleotides 1 to 1499) driven by the LAT promoter is inserted into an ectopic location in the virus.…”
mentioning
confidence: 99%